Virulence factors involved in the pathogenesis of the infection caused by the swine pathogen and zoonotic agent Streptococcus suis. (February 2012) - Fittipaldi, Nahuel; Segura, Mariela; Grenier, Daniel; Gottschalk, Marcelo
Streptococcus suis is a major swine pathogen responsible for important economic losses to the swine industry worldwide. It is also an emerging zoonotic agent of meningitis and streptococcal toxic shock-like syndrome. Since the recent recognition of the high prevalence of S. suis human disease in southeast and east Asia, the interest of the scientific community in this pathogen has significantly increased. In the last few years, as a direct consequence of these intensified research efforts, large amounts of data on putative virulence factors have appeared in the literature. Although the presence of some proposed virulence factors does not necessarily define a S. suis strain as being virulent, several cell-associated or secreted factors are clearly important for the pathogenesis of the S. suis infection. In order to cause disease, S. suis must colonize the host, breach epithelial barriers, reach and survive in the bloodstream, invade different organs, and cause exaggerated inflammation. In this review, we discuss the potential contribution of different described S. suis virulence factors at each step of the pathogenesis of the infection. Finally, we briefly discuss other described virulence factors, virulence factor candidates and virulence markers for which a precise role at specific steps of the pathogenesis of the S. suis infection has not yet been clearly established.